Bullous pemphigoid resembling erythema gyratum repens – case report - Dominiak, Małgorzata P.; Kłosek, Sebastian K.; Gerlicz-Kowalczuk, Zofia; Krzysiek, Joanna; Kobusiewicz, Aleksandra; Kaszuba, Andrzej (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction. Bullous pemphigoid is one of the most common autoimmune bullous dermatoses. It is typically diagnosed in elderly patients and can have various clinical presentations. So far, only individual cases of erythema gyratum repens-like bullous pemphigoid have been described in literature worldwide. Objective. Presentation of the case of a patient with bullae forming a wood grain arrangement. Case report. A 76-year-old female patient hospitalised at the Department of Dermatology with erythematous and edematous figurate lesions and tense bullae on the trunk and extremities. On direct immunofluorescence, complement deposits at the basement membrane zone were found. BIOCHIP indirect immunofluorescence revealed circulating anti-BP180 IgG antibodies. Conclusions . In patients with suspected bullous pemphigoid, direct and indirect immunofluorescence assays are required. As part of the diagnosis of both pemphigoid and erythema gyratum repens, malignancy needs to be excluded as a potential cause of skin lesions. In the presented patient, medical history and additional tests did not demonstrate the presence of a neoplasm. The patient requires further clinical follow-up.